A Review on the Relationship Variables to Customer Satisfaction (Global Journal of Management and Business Research, 2016)
In marketing, customer satisfaction is considered as a key construct in the last few decades. Previously it is a less acceptable construct, since most of the marketing oriented organizations are perceived that attracting new customers better than retaining existing one. However, currently, these organizations are using customer satisfaction as a prime business performance indicator and a weapon in the dynamic environment to get the sustainable competitive advantage. This customer satisfaction is impact by several variables and dimensions. Therefore, this qualitative comprehensive review examines with the variety of literature support the relationship of variables with respect to customer satisfaction. To broaden and make possible further studies contextually and empirically, a mind-map is presented to show how these relationship variables relate to customers satisfaction. This would improve the studies related to customer satisfaction in particular.
Keywords: customer satisfaction; relationship; variables; comprehensive model